Addressing fraction comprehension: global perspectives and Malaysian educational strategies - Syed Ismail, Syed Azman; Maat, Siti Mistima; Khalid, Fariza (International Journal of Evaluation and Research in Education (IJERE), 2025)
Understanding fractions is a significant challenge in mathematics education globally, including in Malaysia, where students often struggle with core concepts. These difficulties hinder their progression into advanced areas like ratios, proportions, and algebra. This paper proposes a conceptual framework to enhance students’ understanding of fractions, with a focus on the Malaysian education system. Drawing on literature and practices from international contexts, this paper emphasizes the importance of visual models, manipulatives, technology integration and real-world applications in teaching fractions. As a concept paper, it synthesizes key insights from educational theories to develop strategies for improving fraction education. The framework highlights the need for alignment with both local and international curriculum. Key findings suggest that the use of manipulatives, visual models and technology can significantly improve fraction comprehension. By comparing global strategies, this paper offers insights into how these methods can be adapted to diverse learning environments, including low-resource settings. The framework implies that curriculum reforms, professional development for teachers and revised assessments are crucial to enhancing student outcomes in fraction education.